2014
DOI: 10.1063/1.4903803
|View full text |Cite
|
Sign up to set email alerts
|

The local crystallization in nanoscale diamond-like carbon films during annealing

Abstract: The local crystallization during annealing at 600 °C in nanoscale diamond-like carbon coatings films grown by pulsed vacuum-arc deposition method was observed using modem techniques of high-resolution transmission electron microscopy. The crystallites formed by annealing have a face-centred cubic crystal structure and grow in the direction [011 ] as a normal to the film surface. The number and size of the crystallites depend on the initial values of the intrinsic stresses before annealing, which in turn depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…However, it can be shown with Eqs. (8), (9) and (11) that samples with no nc-graphite type of sp 2 clusters (n g = 0) have a fixed point at k 0 = Àðb c À b r Þ=ðk c À k r Þ and x 0 = k r k 0 þ b r for arbitrary n r and n c .…”
Section: Parameters In the Linear Dispersion Modelmentioning
confidence: 98%
See 1 more Smart Citation
“…However, it can be shown with Eqs. (8), (9) and (11) that samples with no nc-graphite type of sp 2 clusters (n g = 0) have a fixed point at k 0 = Àðb c À b r Þ=ðk c À k r Þ and x 0 = k r k 0 þ b r for arbitrary n r and n c .…”
Section: Parameters In the Linear Dispersion Modelmentioning
confidence: 98%
“…High-resolution transmission electron microscopy images of nc-graphite have been observed in amorphous carbon samples grown at high substrate temperature [8] or after annealing [9]. Robertson and O'Reilly [4] found that fused aromatic rings are the most stable configuration for the sp 2 phase; Bredas and Street [10] proved that only fused aromatic rings can lead to the 2.0 eV level band gaps observed in amorphous carbon; Matsunuma [11] reproduced Raman spectra from resonant Raman scattering off fused aromatic rings; and Arenall and Liu [12] assigned the Raman peak at 867 cm À1 to vibrations in the clusters of aromatic rings.…”
Section: Introductionmentioning
confidence: 98%
“…It was found that the most promising composite coating, which has optimal properties (high wear resistance, low friction coefficient, high electrical conductivity and transmittance) is a coating based on layers (C-C: 25Au-C) with a total thickness of 250-300 nm, C:25Au layer thickness was 200 nm. As a disadvantage, it is necessary to note rather high internal compressive stresses, which can be significantly reduced by annealing in vacuum [16].…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest is the comparison with the results obtained in Ref. [15], which describe local crystallization in a diamond-like carbon coating after annealing at 600 • C.…”
Section: Introductionmentioning
confidence: 91%